2023
DOI: 10.1111/iwj.14442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrocolloid dressing on pressure ulcer in patients with non‐invasive positive pressure ventilation: A meta‐analysis

Yu‐Lan Luo,
Shi‐Feng Luo,
Lin Luo
et al.

Abstract: This study systematically evaluated the effect of hydrocolloid dressings on facial pressure ulcers in patients receiving non‐invasive positive pressure ventilation (NIPPV). The Embase, PubMed, Cochrane Library, CNKI, VIP, Chinese Biomedical Literature Database and Wanfang databases were searched for randomised controlled trials on the use of hydrocolloid dressings in patients receiving NIPPV published from the inception of each database to August 2023. The literature was independently screened, data were extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“… 1 The prolonged pressure from NIV masks can lead to skin breakdown, causing discomfort, increasing the risk of infection and potentially complicating the patient's clinical course. 1 , 2 Traditional methods to mitigate this issue have included regular skin care and the use of barrier dressings, such as gauze. 3 However, recent studies have suggested that hydrocolloid dressings may offer superior protection against pressure ulcers due to their unique properties in maintaining moisture balance and promoting healing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 The prolonged pressure from NIV masks can lead to skin breakdown, causing discomfort, increasing the risk of infection and potentially complicating the patient's clinical course. 1 , 2 Traditional methods to mitigate this issue have included regular skin care and the use of barrier dressings, such as gauze. 3 However, recent studies have suggested that hydrocolloid dressings may offer superior protection against pressure ulcers due to their unique properties in maintaining moisture balance and promoting healing.…”
Section: Introductionmentioning
confidence: 99%
“…Facial pressure ulcers are a significant complication for patients undergoing non‐invasive ventilation (NIV), particularly in critical care settings 1 . The prolonged pressure from NIV masks can lead to skin breakdown, causing discomfort, increasing the risk of infection and potentially complicating the patient's clinical course 1,2 . Traditional methods to mitigate this issue have included regular skin care and the use of barrier dressings, such as gauze 3 .…”
Section: Introductionmentioning
confidence: 99%